A nearly on‐axis spectroscopic system for simultaneously measuring UV–visible absorption and X‐ray diffraction in the SPring‐8 structural genomics beamline. (3rd December 2015) - Sakaguchi, Miyuki; Kimura, Tetsunari; Nishida, Takuma; Tosha, Takehiko; Sugimoto, Hiroshi; Yamaguchi, Yoshihiro; Yanagisawa, Sachiko; Ueno, Go; Murakami, Hironori; Ago, Hideo; Yamamoto, Masaki; Ogura, Takashi; et al.
Abstract : UV–visible absorption spectroscopy is useful for probing the electronic and structural changes of protein active sites, and thus the on‐line combination of X‐ray diffraction and spectroscopic analysis is increasingly being applied. Herein, a novel absorption spectrometer was developed at SPring‐8 BL26B2 with a nearly on‐axis geometry between the X‐ray and optical axes. A small prism mirror was placed near the X‐ray beamstop to pass the light only 2° off the X‐ray beam, enabling spectroscopic analysis of the X‐ray‐exposed volume of a crystal during X‐ray diffraction data collection. The spectrometer was applied to NO reductase, a heme enzyme that catalyzes NO reduction to N2 O. Radiation damage to the heme was monitored in real time during X‐ray irradiation by evaluating the absorption spectral changes. Moreover, NO binding to the heme was probed via caged NO photolysis with UV light, demonstrating the extended capability of the spectrometer for intermediate analysis.